Providing azolla and goat manure to increase nutrient N and growth of lowland rice (Oryza sativa L.) - Qori Hafizah,; Hamidah Hanum,; Damanik, Mohd. Madjid B. (Jurnal Online Pertanian Tropik, 2020)
One of the problems in the paddy field is the lack of availability of nutrient N in paddy soil, it can be overcome by giving azolla and goat manure. The aimis to determine the effect of giving azolla and goat manure for increasing the nutrient N and the growth of rice plants. This research used factorial Random Group Design (RAK) with two treatment factors and three replications. The first factor is azolla dose (0, 7 tons / ha) and the second factor is goat manure dose (0, 5, 10, 15 tons / ha). This research is implemented in the greenhouse of the Faculty of Agriculture, University of North Sumatra, Medan. The result of the study indicated giving of azolla increased C-organic, N-total, N content, and N uptake of plant. Giving goat manure at a dose of 15 tons/ha increased C-organic, number of tillers, canopy dry weight, root dry weight, N content of N uptake. Providing azolla and goat manure 5 tons/ha the highest increased N uptake of plants and growth of lowland rice plants. REFERENCES Abu R.L.A., Z. Basri, U. Made. 2017. Response of Growth and Yield of Rice (Oryza sativa L.). Of Nitrogen Needs Using Leaf Color Bgn. Faculty of Agriculture's Agrotechnology Study Program. Tadulako University. BPS North Sumatra. 2018. Harvested Area and Rice Production in North Sumatra. BPPP. 2006. Organic fertilizers and biological fertilizers. Center for Research and Development of Agricultural Land Resources. West Java. Handayani, M. 2011. Utilization of Goat Manure and Rice Husk Ash to Reduce the Use of Urea and KCl Fertilizers and Their Effects on the Growth of Rice Plants and the Chemical Properties of Paddy Soils. Faculty of Agriculture, University of North Sumatra. Field. Nurmayulis, U. P, F. Dewi, Y. Hasnan, and C. Ania.2011. The Response of Nitrogen and Azolla to Mira I Varieties Rice Plant Growth with SRI Method. Scientific Journal of Isotope and Radiation Applications .ISSN 1907-0322. Rauf, A. W., Syamsuddin., S. R. Sihombing. 2000. Role of NPK Fertilizers in Rice Plants. Agriculture department. Agricultural Research and Development Agency. West Koya Agricultural Technology Study Workshop. Irian Jaya. Setiawati M. R. 2014. Increased N and P Content of Soil and Paddy Rice Results Due to Application of Azolla and Biotertilizer Azotobacter chroococcum and Pseudomonas cepaceae. Faculty of Agriculture. Padjadjaran University. Bandung. Setyorini, D ,. Sri, R, .and Irsal, L. 2010. Agriculture in Wetland Ecosystems in Reversing the Degradation of Land Resources and Water Degradation. Agricultural Research and Development Agency. Ministry of Agriculture. Suharyanto and J. Rinaldi, 2002. Estimation of the Potential and Economic Value of Manure in Bali. Institute for Agricultural Technology Assessment (BPTP), Bali. Sudjana, B ,. 2014. Use of Azolla for Sustainable Agriculture. Singapore University of Krawang. Bandung. Scientific Journal of Solutions 1 (2) 72-81 April-June 2014. Soedharmono, G.G., S.Y. Tyasmoro and H.T., Sebayang. 2016. The effect of giving azolla fertilizer and N fertilizer on rice (Oryza sativa L.) Inpari rice varieties, Faculty of Agriculture, Brawijaya University, East Java. Journal of crop production 4 (2) 145: 152 March 2016. Syamsiah, J., Hendro., B.S., and Mujiyo. 2016. Potential of Azolla as Substitution of Manure on Organk Rice Cultivation. Soil Science Study Program, Faculty of Agriculture, Sebelas Maret University. Surakarta